Protein-protein interaction between a candidate effector of S. scitamineum and a transcription factor of A. thaliana to study the smut-sugarcane pathosystem - Mendes, Jéssica Fernanda (2022)
Sugarcane is a crop of great economic value. It is possible to generate ethanol, bioplastics, hydrocarbons and biogas from the production of sugarcane. Sugarcane\'s genetic material is very complex, being polyploid and with several transposable elements. Although there are resistant varieties of sugarcane, this crop can undergo significant economic losses because of diseases. The sugarcane smut disease is caused by the biotrophic fungus Sporisorium scitamineum, and its main symptom is the development of a whip formed by teliospores of the fungus and plant&#8217s tissues. After infection, sugarcane goes through an extensive transcriptional change. The pathogen uses effectors to assist penetration and colonization into the host\'s tissues. This study aimed to validate an interaction between the candidate effector g5159 previously described from our research group and a transcription factor SPL13. The first chapter consists in a bibliographic review of main concepts discussed in the dissertation. The tSPL13 is part of the SQUAMOSA-PROMOTER BINDING PROTEIN-like transcription factor family, and it is involved in the transition phases of the plant, such as to the vegetative and reproductive phases. The CE g5159 and AtSPL13 interaction was previously shown through a Yeast-Two-Hybrid assay in our group and now we used bimolecular fluorescence complementation (BiFC) assay to validade this protein- protein interaction. We used SPL13 from Arabidopsis thaliana and we are currently working on SPL13 PCR-amplification of RB925354, SP80-3280 and IAC66-6 varieties of sugarcane. Arabidopsis thaliana is extensively used as a model plant because of its complete genome sequencing and facility to manipulate the plant. In the second chapter we showed our BiFC assay results, indicating that the CE g5159 and AtSPL13 interaction occurred. We also speculate that CE g5159 may retain AtSPL13 subcellular location from the nucleus. However, future research is necessary to better comprehend the mechanism. In the last chapter we inferred phylogenetic relationships among sugarcane SPLs orthologs and other flowering species. Orthologs of SPL13 from A. thaliana and sugarcane clustered in the same clade and their alignment showed conserved regions between SPL13 from A. thaliana and sugarcane cultivars. We also used published transcriptome data to uncover the expression patterns of SPLs in infected sugarcane. This is the first study to show a protein-protein interaction between a candidate effector from S. scitamineum and a transcription factor involved in the vegetative and reproductive growth of the plant. Our results allow future investigation within molecular mechanisms used by the fungus to better understand the pathosystem and to advance in breeding programs.